Determination of Small Parameter of Auto-Oscillating «Single-Phase Asynchronous Motor – Linear Elastic Element» System - V. I. Lukovnikov; Y. A. Rudchenko; N. V. Samovendyuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Expression for detection of a small parameter has been obtained in the paper. The parameter determines proximity of auto-oscillating «single-phase asynchronous electric motor – linear elastic element» system to linear conservative one. The given expression can be used for determination of an error which is given by an asymptotic method for analysis of the auto-oscillating system described in the given paper (in particular the Van der Pol method).